PENGARUH DESENTRALISASI FISKAL, SISTEM PENGENDALIAN INTERNAL DAN KINERJA PEMERINTAH DAERAH TERHADAP AKUNTABILITAS LAPORAN KEUANGAN - Purbasari, Heppy; Bawono, Andy Dwi Bayu (Universitas Muhammadiyah Surakarta, 2017)
AbstractThis research aims to examine an impact of fiscal decentralization, internal control system, and local government performance examination to the local government financial accountability. As Local autonomy implemented in Indonesia in 1999, it has impacted to several financial reform in Indonesia such as fiscal decentralization calculation, new model of internal control system, new criteria of local government performance and also local financial report accountability. This study collected secondary data from Badan Pemeriksa Keuangan Republik Indonesia by using 117 local government in Java Island as population. The study used purposive sampling method that consists of 106 local government that were analyzed by linear regression by using SPSS 21. The result showed that internal control system has significant impact to the local government financial accountability. However, fiscal decentralisation and local government performance examination has no significant influence to local government financial accountability.Keywords: decentralisation fiscal, internal control system, local government performance, local government financial accountability.